2019
DOI: 10.1186/s13717-019-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Resources development and tourism environmental carrying capacity of ecotourism industry in Pingdingshan City, China

Abstract: Background: Pingdingshan City has unique and rich ecotourism landscape. To realize the sustainable development of ecotourism industry in Pingdingshan and simultaneously achieve economic development and environmental protection in the development of ecotourism resources, literature analysis and field investigation methods were used to deeply explore the advantages and problems of Pingdingshan in the process of resources development in this study. Then, the indicator system of environmental carrying capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…The ecotourism natural carrying capacity framework consists of four components: asset natural carrying capacity, biology natural carrying capacity, brain research natural carrying capacity, and tourist natural carrying capacity. The value of ecotourism's natural carrying capacity is not the sum of its parts, but rather the lowest value assigned to each part (Zhao & Jiao, 2019).…”
Section: Building Based On Carrying Capacitymentioning
confidence: 99%
“…The ecotourism natural carrying capacity framework consists of four components: asset natural carrying capacity, biology natural carrying capacity, brain research natural carrying capacity, and tourist natural carrying capacity. The value of ecotourism's natural carrying capacity is not the sum of its parts, but rather the lowest value assigned to each part (Zhao & Jiao, 2019).…”
Section: Building Based On Carrying Capacitymentioning
confidence: 99%
“…Regarding ecotourism, it is possible to find several academic studies. Some studies focus on ecotourism as a learning tool (Mondino, Beery, 2019), role of ecotourism in sustainable tourism development (Salman et al, 2020), ecotourism potential of destinations (Safarabadı, 2016;Güler, 2021), carrying capacity within ecotourism (Butarbutar, Soemarno, 2013;Zhao, Jiao, 2019)planningand design (Shang et al, 2020;Sisriany,Furuya, 2020;Aryal et al, 2019;Cohen, Silva, 2010), research topics benefiting from meta-analysis (Wondirad, 2019), tourists' intention to participate in ecotourism (Pham, Khanh, 2020;Ren et al, 2021;Lee et al, 2020;Handriana, Ambara, 2016), intentions of locals/residents toparticipate in ecotourism (Wu, Chen, 2018;Landra et al, 2018;Mogoria et al, 2018;Lim et al, 2017;Wanga et al, 2013;Menon, 2019;Adeleke, 2015;Zhang, Lei, 2012). Mondino and Beery (2019) have investigated ecotourism as a learning tool benefiting from a case study and have found out that ecotourism activities supported collaboration between stakeholders, but because of insufficient environmental education (language, method, and course related problems at higher governmental levels) there were still negative perceptions of the sides.…”
Section: Ecotourismmentioning
confidence: 99%
“…Industri ekowisata di Indonesia telah mencapai perkembangan pesat berdasarkan sumber daya ekowisata yang baik. Perlindungan sumber daya ekowisata dapat secara efektif mempromosikan pengembangan industri pariwisata yang berkelanjutan, termasuk didalamnya pertumbuhan industry pariwisata yang menciptakan peluang ekonomi tambahan bagi warga sekitar dan industry local di sekelilingnya (Zhao and Jiao 2019). Di sisi lain, alam memiliki daya dukung yang didalam toeri Daya Dukung atau Carriying Capacity dijelaskan sebagai pemahaman daya dukung suatu lingkungan adalah ukuran populasi maksimum suatu spesies biologis yang dapat dipertahankan dalam lingkungan spesifik tersebut, dengan mempertimbangkan makanan, habitat, air, dan sumber daya lain yang tersedia.…”
Section: Kemampuan Daya Dukung Tempatunclassified